Evaluation of different modulus input on the mechanical responses of asphalt pavement based on field measurements. (20th December 2021) - Qian, Guoping; Shi, Changyun; Yu, Huanan; Yao, Ding; Zhu, Xuan; Li, Xi
Highlights: The field mechanical responses were evaluated based on FBG sensors and deflection test. 11 types of material moduli were obtained through various modulus tests. A FEM model under different moduli was established to evaluate the mechanical responses of pavement. The optimum modulus tests were obtained base on the comparison between FEM and field. Abstract: As a key input parameter of asphalt pavement design, the modulus parameters directly affect the results of pavement stress analysis. During the mechanical evaluation analysis, researchers usually use material modulus instead of structural modulus as input parameter, so the possible deviations between the field measured mechanical responses and the calculated responses are ignored in this case. Therefore, the field mechanical response and the calculations mechanical response of finite element method (FEM) with different moduli input were evaluated in this research. The field strains of each pavement layer under dynamic and static load conditions were determined by embedding the fiber Bragg grating (FBG) sensors, and the field deflection test was carried out by Beckman beam. A total of 11 types of material moduli were obtained through various modulus tests, and which were implemented in the FEM model for the strain and deflection calculation of pavement structure, and then the calculated mechanical responses were compared with the field measured mechanical responses. The results indicated that a specific modulus should be selected to ensure the calculated value effectively reflect the measured mechanical response. For the FEM calculation of dynamic strain, it is recommended to use static flexural modulus for asphalt layer and use dynamic flexural modulus for CSG layer as modulus input with average errors of 16.9% and 7.5% respectively. For the FEM calculation of static strain, it is recommended to use dynamic compressive resilience modulus for asphalt layer and use static flexural modulus for CSG layer as modulus input with average errors of 18.7% and 11.5% respectively. Besides, it is recommended to select dynamic flexural modulus or compressive modulus in static four-point bending test as the modulus input for pavement deflection analysis with the error of about 4.8%.